Obesity and risk of death or dialysis in younger and older patients on specialized pre-dialysis care. - Ellen K Hoogeveen; Kenneth J Rothman; Pauline W M Voskamp; Renée de Mutsert; Nynke Halbesma; Friedo W Dekker; PREPARE-2 Study Group (PLoS ONE)
Background Obesity is associated with increased mortality and accelerated decline in kidney function in the general population. Little is known about the effect of obesity in younger and older pre-dialysis patients. The aim of this study was to assess the extent to which obesity is a risk factor for death or progression to dialysis in younger and older patients on specialized pre-dialysis care. Method In a multicenter Dutch cohort study, 492 incident pre-dialysis patients (>18y) were included between 2004-2011 and followed until start of dialysis, death or October 2016. We grouped patients into four categories of baseline body mass index (BMI): <20, 20-24 (reference), 25-29, and ≥30 (obesity) kg/m2 and stratified patients into two age categories (<65y or ≥65y). Results The study population comprised 212 patients younger than 65 years and 280 patients 65 years and older; crude cumulative risk of dialysis and mortality at the end of follow-up were 66% and 4% for patients <65y and 64% and 14%, respectively, for patients ≥65y. Among the <65y patients, the age-sex standardized combined outcome rate was 2.3 times higher in obese than those with normal BMI, corresponding to an excess rate of 35 events/100 patient-years. After multivariable adjustment the hazard ratios (HR) (95% CI) for the combined endpoint by category of increasing BMI were, for patients <65y, 0.92 (0.41-2.09), 1 (reference), 1.76 (1.16-2.68), and 1.81 (1.17-2.81). For patients ≥65y the BMI-specific HRs were 1.73 (0.97-3.08), 1 (reference), 1.25 (0.91-1.71) and 1.30 (0.79-1.90). In the competing risk analysis, taking dialysis as the event of interest and death as a competing event, the BMI-specific multivariable adjusted subdistribution HRs (95% CI) were, for patients <65y, 0.90 (0.38-2.12), 1 (reference), 1.47 (0.96-2.24) and 1.72 (1.15-2.59). For patients ≥65y the BMI-specific SHRs (95% CI) were 1.68 (0.93-3.02), 1 (reference), 1.50 (1.05-2.14) and 1.80 (1.23-2.65). Conclusion We found that obesity in younger pre-dialysis patients and being underweight in older pre-dialysis patients are risk factors for starting dialysis and for death, compared with those with a normal BMI.